Pemberian Cendawan Mikoriza Arbuskular (CMA) pada Tanah Podzolik Merah Kuning (PMK) terhadap Pertumbuhan dan Produksi Kedelai (Glycine max (L) Meriil) - Elza Zuhry; Fifi Puspita (Jurnal Sagu, 2008)
The objective of this research was to achieve the best CMA dosage for soybean growth and production in red yellow podzolic soil. This research was carried out experimentally by Completely Randomized Design (CRD) which consisted of 5 treatments (0 g CMA/plant, 10g CMA/plant, 20g CMA/plant, 30g CMA/plant, dan 40g CMA/plant) and 4 replications. Parameters observed were CMA infection percentage (%), the age of flower bloom (day), the age of harvesting time (day), amount of pods (pods), and seed dry weight (g).  The analysis of Variance was followed by Duncan’s New Multiple Range Test at 5% level. The result of this research concluded that application of 40g CMA/plantin red yellow podzolic soil will increase soybean growth and production.